Information and rumor in conflict areas (2007)
Information sources, creation of informant networks and labors of local intelligence have become very important goals in political power calculations of the paramilitary and insurgents. Phenomena of information and rumor can disclose central aspects to understand the direction of events yet to be seen in local politics. The text presents a phenomenological analysis of information (and its deviations) to understand the dynamics of armed conflict at a local level.